2019
DOI: 10.1016/j.devcel.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

An SH3PX1-Dependent Endocytosis-Autophagy Network Restrains Intestinal Stem Cell Proliferation by Counteracting EGFR-ERK Signaling

Abstract: Highlights d A Drosophila SH3PX1-dependent endocytosis-autophagy network restrains ISC division d Endocytosis and autophagy control ISC division by counteracting EGFR-ERK activity d Genes in endocytosis and autophagy are frequently mutated in human cancers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
82
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 83 publications
13
82
1
Order By: Relevance
“…This study demonstrated that blockages within the endocytosis-autophagy network stabilize ligand-activated EGFRs. This blocks the recycling of EGFRs to the plasma membrane and, in turn, counteracts EGFR signaling (Zhang et al, 2019). However, the biological functions and the physiological significance of the endocytic pathway in the context of ISC aging remain inadequately understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that blockages within the endocytosis-autophagy network stabilize ligand-activated EGFRs. This blocks the recycling of EGFRs to the plasma membrane and, in turn, counteracts EGFR signaling (Zhang et al, 2019). However, the biological functions and the physiological significance of the endocytic pathway in the context of ISC aging remain inadequately understood.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study demonstrated that endocytosis works downstream of ALA in ISCs to protect the degeneration of intestinal function upon aging. A recent study indicated EGFR signaling as the main trigger for ISC overproliferation when the endocytosis-autophagy network was disturbed (Zhang et al, 2019). Therefore, this study investigated the EGFR activity of ISCs of Drosophila in response to ALA administration by monitoring the dpERK level.…”
Section: Ala Administration Rejuvenates Aged Iscs By Modulating Endocmentioning
confidence: 99%
“…Because homeostatic control of proliferation occurs broadly in the animal kingdom and because regulators of stem cell proliferation and homeostasis are highly conserved (ERK/MAPK and IIS, see Introduction), these regulators may similarly combine to orchestrate stem cell proliferation rates in diverse stem cell populations. Consistent with this, GSC proliferation in Drosophila is stimulated by nutrient uptake via IIS signaling 33 , while homeostatic regulation of intestinal stem cells occurs through ERK/MAPK regulation 61 .…”
Section: Discussionmentioning
confidence: 56%
“…Our studies reveal that ISCautonomous defects in the endocytosis-autophagy network (including shi/dynamin, Rab5, Rab7, SH3PX1, Atg1, Atg5, Atg6, Atg7, Atg8a, Atg9, Atg12, Atg16 and Syx17) release ISC proliferation without regulating differentiation, potentially increasing cancer risk. We provide a detailed functional analysis of how a conserved process (autophagic flux) controls a classical growth signaling pathway (Egfr-Ras85D-mitogenactivated protein kinase), and how genes in this process (some poorly characterized, like SH3PX1) can be anti-proliferative and tumor-suppressive [1].…”
Section: Isc-autonomous Autophagy Defects Release Stem Cell Proliferamentioning
confidence: 99%